Effect of melting temperatures on the crystallization and densification of 2.8MgOÂ•1.5Al2O3Â•5SiO2 glass-ceramic synthesized from mainly talc and kaolin - Banjuraizah, Johar; Hasmaliza, Mohamad; Zainal Ariffin, Ahmad (Elsevier B. V., 2011)
Link to publisher's homepage at http://www.elsevier.com/